2018
DOI: 10.1021/acssensors.8b00340
|View full text |Cite|
|
Sign up to set email alerts
|

Hacking CD/DVD/Blu-ray for Biosensing

Abstract: The optical pickup unit (OPU) within a CD/DVD/Blu-ray drive integrates 780, 650, and 405 nm wavelength lasers, diffraction-limited optics, a high-bandwidth optoelectronic transducer up to 400 MHz, and a nanoresolution x-, z-axis, and tilt actuator in a compact size. In addition, the OPU is a remarkable piece of engineering and could enable different scientific applications such as sub-angstrom displacement sensing, micro- and nanoimaging, and nanolithography. Although off-the-shelf OPUs can be easily obtained,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(35 citation statements)
references
References 81 publications
0
35
0
Order By: Relevance
“…Many studies have applied it as an optical device, such as an optical microscope 13 , for measuring the thermal vibration of a microcantilever for atomic force microscopy 14 . The OPU is also useful for refractive index measurement at the femtoliter scale 15 and a biological sensor at the nano-and micro-scale levels 16 due to its various functions. It has also been applied in micropatterning devices 17 , optical fluid scanning to detect protein aggregation in microfluidics 18 , and DNA replication using magnetic nano-beads 19 .…”
mentioning
confidence: 99%
“…Many studies have applied it as an optical device, such as an optical microscope 13 , for measuring the thermal vibration of a microcantilever for atomic force microscopy 14 . The OPU is also useful for refractive index measurement at the femtoliter scale 15 and a biological sensor at the nano-and micro-scale levels 16 due to its various functions. It has also been applied in micropatterning devices 17 , optical fluid scanning to detect protein aggregation in microfluidics 18 , and DNA replication using magnetic nano-beads 19 .…”
mentioning
confidence: 99%
“…4. The surface scanning device includes precision rotary platform with a piezoelectric actuator and aerostatic suspension [24,16]. A laser scanning head, primary photoreceiver and signal amplifiers were placed on the top of the rotary platform.…”
Section: Experimental Results Of the Angle Encoder Disc Calibrationmentioning
confidence: 99%
“…Some approaches deal with the application fields such as accelerometry, profilometry and linear measurements [13][14][15]. Latest research suggests that CD and DVD pick up heads have a lot of potential for the instrumentation development in biochemistry and biosensing [16,17]. However, it was not applied for the determination of an angle encoder disc surface quality measurements.…”
Section: ⇑ Corresponding Authormentioning
confidence: 99%
“…Therefore, a new technique of low cost, easy process, and scratch detectability has been presented by using ordinary laser doppler and CD pick-up head to inspect surface details because of its advantages on the measurement of object roughness and the identification of scratch location, in a compromising process [8,9]. Moreover, numerous studies have recently shown interesting results of using DVD pick-up head to detect the reflective DNA layers on a DNA chip slide as its potentiality to show the shape of the DNA and count the number of cells [10]. The DVD pick-up head has been developed for better precision by reflecting the beam to photo detector integrated chip (PDIC), as a receiver, and then, the reflected laser light from PDIC is focused and analyzed on four quadrant sensors of photodiode detector [11].…”
Section: Introductionmentioning
confidence: 99%